PENGEMBANGAN BUDIDAYA LEBAH MADU KELULUT (Trigona sp) DI PESANTREN MIFTAHUL ULUM TABALONG - Trisnu Satriadi; Susilawati Susilawati; Badaruddin Badaruddin; Eko Suhartono; Rahmiyati Rahmiyati (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract The Miftahul Ulum Islamic Boarding School in Bangkiling Raya Village is one of the Islamic boarding schools whose students do not yet have many soft skills, one of which is as an entrepreneur. The Service Team from ULM together with PT Adaro Indonesia through the Grand Matching Fund program plans to carry out community service activities at that location with the material of kelulut honey bee cultivation. Service activities carried out include preliminary survey activities, socialization or counseling, training and mentoring. During the survey, the service team was well received by village officials and partners and they were very enthusiastic about participating in this service activity. The socialization activity was carried out by the service team with KKN students from ULM and went well. The training provided to partners includes the cultivation of kelulut honey bees, namely the management of kelulut honey bee cultivation. Mentoring activities include accompanying partners from cultivation to harvesting and marketing assisted by KKN students. From the results of community service activities there is a problem, namely honey colonies that do not develop. To overcome this problem, the service team conducts socialization and training on solving kelulut bee colonies and care management so that the colony develops well. In addition, the team also provided motivation to be passionate about cultivating kelulut honey bees. Keywords: bees; Trigona sp; cultivation; additional stup; Grand Matching Fund Abstrak Pondok Pesantren Miftahul Ulum yang berada di Desa Bangkiling Raya merupakan salah satu ponpes yang santrinya belum memiliki banyak soft skills salah satunya sebagai seorang wirausaha. Tim Pengabdi dari ULM bersama PT Adaro Indonesia melalui program Grand Matching Fund telah melaksanakan kegiatan pengabdian di lokasi tersebut dengan materi budidaya lebah madu kelulut. Kegiatan pengabdian yang dilakukan meliputi kegiatan survey pendahuluan, sosialisasi atau penyuluhan, pelatihan dan pendampingan. Selama survey, tim pengabdi diterima dengan baik oleh aparat desa dan mitra serta mereka sangat antusias untuk mengikuti kegiatan pengabdian ini. Kegiatan sosialisasi dilakukan tim pengabdi bersama mahasiswa KKN dari ULM dan berjalan dengan baik. Pelatihan yang diberikan kepada mitra meliputi budidaya lebah madu kelulut yaitu manajemen budidaya lebah madu kelulut. Kegiatan pendampingan meliputi mendampingi mitra dari budidaya hingga pemanenan dan pemasaran dibantu oleh mahasiswa KKN. Dari hasil kegiatan pengabdian terdapat masalah yaitu koloni madu yang tidak berkembang. Untuk mengatasi masalah ini, tim pengabdi melakukan sosialisasi dan pelatihan mengenai pemecahan koloni lebah kelulut serta manajemen perawatan agar koloni berkembang dengan baik. Selain itu, tim juga memberikan motivasi agar semangat dalam membudidayakan lebah madu kelulut. Kata Kunci: lebah; Trigona sp; budidaya; penambahan stup; Grand Matching Fund